Toward a theory of monopolistic competition - Philip Ushchev; Mathieu Parenti; Jacques-Francois Thisse (European Regional Science Association (ERSA), 2014)
We propose a general model of monopolistic competition, which encompasses existing models while being flexible enough to take into account new demand and competition features. Using the concept of Frechet differentiability, we determine a general demand system. The basic tool we use to study the market outcome is the elasticity of substitution at a symmetric consumption pattern, which depends on both the per capita consumption and the total mass of varieties. We impose intuitive conditions on this function to guarantee the existence and uniqueness of a free-entry equilibrium. Our model is able to mimic oligopolistic behavior and to replicate partial equilibrium results within a general equilibrium framework. For example, an increase in per capita income or in population size shifts prices (outputs) downwards (upwards). When firms face the same productivity shock, they adopt an incomplete pass-through policy, except when preferences are homothetic. Finally, we show how our approach can be generalized to the case of a multisector economy and extended to cope with heterogeneous firms and consumers.
Keywords: D43; L11; L13; 330; monopolistic competition; general equilibrium; additive preferences; homothetic preferences